Client Pressures, Audit Tenure to Audit Quality: Moderation of Auditor Independence - Muslim Muslim; Hamzah Ahmad; Syamsuri Rahim; Muhammad Faisal ARPelu (Master of Accounting Universitas Trunojoyo Madura, 2020)
This study aims to examine the effect of client pressure and audit tenure on audit quality with auditor independence as a moderating variable in the Public Accounting Firm (KAP) in Makassar. The data in this study were obtained from each KAP in Makassar City who were willing to become respondents. This study uses primary data by conducting direct research in the field by providing questionnaires/question sheets to 45 respondents. The data analysis method used is moderated regression analysis (MRA). The results showed that client pressure had a positive and significant effect on audit quality. While the audit tenure variable has a negative and significant effect on audit quality. Auditor independence variable is a moderating variable that affects client pressure and audit quality